Synthesis and Crystal Structure of [1,2-bis(4-(Pyridine-2-yl)pyrimidine-2-ylthio)ethane- k4N,N,N',N'] bis[Diiodidocadmium(II)]: (CdI2)2C20H16N6S2·(CHCl3)2 - Hu, Da-Hua; Dong, Hua-Ze (Asian Journal of Chemistry, 2010)
A novel 3D supramolecular complex [1,2- bis(4-(pyridine-2-yl)pyrimidine-2-ylthio)ethane- k4N,N,N',N'] bis[Diiodidocadmium(II)] with molecular formula as (CdI2)2C20H16N6S2·(CHCl3)2, was synthesized by the reaction of 1,2-bis(4-(pyridin-2-yl)pyrimidin-2-ylthio)ethane with CdI2, in which each ligand connects two identical Cd ions in N,N' chelation modes to form a discrete dinuclear cadmium coordination complex, which crystallizes in the monoclinic space group P-1. The coordination geometry around each Cd(II) cation is a distorted tetrahedron completed by two N atoms from one arm and two I atoms. Both pyridyl and pyrimidyl rings at the end of each arm are not coplanar with a deviation of 4.6°. The average Cd-N and Cd-I bond lengths are 2.310 and 2.667 Å, respectively. The crystal packing also exhibits weak intermolecular C-H···I hydrogen bonds. The crystal is monoclinic, space group P-1 with unit cell parameters: a = 8.2429(13) Å, b = 9.5001(15) Å, c = 13.633(2) Å, a = 81.843(3)º, b = 78.902(3)º, g = 68.244(2)º, V = 970.1(3)Å3, Z = 1, Mr = 1375.68, Dc = 2.355 g/cm3, μ = 4.824 mm-1, F(000) = 634.0, R = 0.0735, wR = 0.2298 for 3353 reflections with I > 2s(I).